METALS HEAT TREATMENT MODEL (Modern Problems of Metallurgy, 2020)
This paper considers the problem of developing a model of thermal metal processing by multiprocessor computing systems. The obtained metal is used for high-strength fasteners manufactured by cold forging method without final heat treatment. The model is based on the heat treatment method of a billet from low- and medium-carbon steels intended for cold heading. The model aims at improving technological properties of a billet by ensuring high dispersion and uniformity of a billet structure across the entire plane of its cross-section.Implementation of the proposed model ensures the technical result of high dispersion and uniformity of the structure of the billet. The technological process of steel heat treatment is characterized by high performance, low power consumption, and improved performance characteristics. The apparatus for implementation of the spheroidization annealing regime determines the uniform distribution of cementite globules in the ferrite matrix, which means that it provides the necessary mechanical properties of the metal for its further cold deformation. The multiprocessor computing system software allows controlling the temperature conditions, both on the entire plane of the billet section, and across its length. Such temperature conditions are controlled in the center of the plane of the billet cross-section.Experimental studies of the heat treatment of metal products were conducted. In order to test the functions of the proposed model, several experiments were performed when a 20 mm diameter wire from 20G2G steel was subjected to heat treatment. Experimental studies have shown that metal has the necessary elasticity properties, saving the required hardness.
Keywords: heat treatment, multiprocessor computing system, mathematical model, parameter control, technological process, temperature regime